∫ 1 ∞ x 3 ⌊ x ⌋ d x = a 3 + 1 2 π b + 2 4 π 2 c − 1
The equation above holds true for where a , b and c are integers a , b and c . Compute the value of c a + b .
Notation: ⌊ ⋅ ⌋ denotes the floor function .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Well done!
Log in to reply
[ This message has been retracted ]
Log in to reply
Sure! I'd be glad to :)
Log in to reply
@Diego G – Go here . Let me know once you registered and logged in to it.
In your solution after noting that,
I = ∑ k = 1 ∞ k × ∫ k k + 1 x 3 1 d x
We can rewrite that as,
I = ∑ k = 1 ∞ ∫ k ∞ x 3 1 d x
which is 2 1 × ζ ( 2 )
I = ∫ 1 ∞ x 3 ⌊ x ⌋ d x = k = 1 ∑ ∞ ∫ k k + 1 x 3 k d x = k = 1 ∑ ∞ − 2 x 2 k ∣ ∣ ∣ ∣ k k + 1 = 2 1 k = 1 ∑ ∞ ( k 2 k − ( k + 1 ) 2 k ) = 2 1 k = 1 ∑ ∞ ( k 1 − ( k + 1 ) 2 k + 1 − 1 ) = 2 1 k = 1 ∑ ∞ ( k 1 − k + 1 1 + ( k + 1 ) 2 1 ) = 2 1 ( 1 1 ) + 2 1 k = 1 ∑ ∞ ( k + 1 ) 2 1 = 2 1 + 2 1 k = 1 ∑ ∞ k 2 1 − 2 1 = 1 2 π 2
Therefore, a 3 + 1 2 π b + 2 4 π 2 c − 1 = 3 3 + 1 2 π ⋅ 0 + 2 4 π 2 ⋅ 2 − 1 ⟹ c a + b = 2 3 + 0 = 8 .
I = 1 ∫ ∞ x 3 ⌊ x ⌋ d x = k = 1 ∑ ∞ 0 ∫ 1 ( k + x ) 3 k d x = − k = 1 ∑ ∞ 2 k [ ( k + 1 ) 2 1 − k 2 1 ] = − k = 1 ∑ ∞ 2 k [ ( k + 1 ) 2 k 2 − 2 k − 1 ] = 2 1 k = 1 ∑ ∞ [ ( k + 1 ) 2 2 + ( k + 1 ) 2 k 1 ] = 2 1 [ 2 ( π 2 / 6 − 1 ) + 2 − π 2 / 6 ] = π 2 / 1 2 = 3 3 + 2 4 2 π 2 − 1
So c a + b = 2 3 + 0 = 8
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Integration of Piecewise Functions
Let n be an integer . If n ≤ x < n + 1 , then ⌊ x ⌋ = n . And we denote I as the integral in question. We have
I = = = = = = = ∫ 1 ∞ x 3 ⌊ x ⌋ d x ∫ 1 2 x 3 1 d x + ∫ 2 3 x 3 1 d x + ∫ 3 4 x 3 1 d x + ⋯ + ∫ n n + 1 x 3 1 d x + ⋯ m = 1 ∑ ∞ ∫ m m + 1 x 3 m d x m = 1 ∑ ∞ m ⋅ [ − 2 x 2 1 ] m m + 1 m = 1 ∑ ∞ 2 1 ⋅ [ − ( m + 1 ) 2 m + m 2 m ] 2 1 m = 1 ∑ ∞ ⋅ [ m 1 − m + 1 1 + ( m + 1 ) 2 1 ] 2 1 = 1 m = 1 ∑ ∞ ( m 1 − m + 1 1 ) + 2 1 = π 2 / 6 − 1 m = 1 ∑ ∞ ( m + 1 ) 2 1 = 1 2 π 2 .
We can evaluate the two series in the penultimate step above by noticing that the first series is a telescoping series , and the second series can be expressed as ζ ( 2 ) − 1 , where ζ ( ⋅ ) denotes the Riemann Zeta function .
Now, we want to express I = 1 2 π 2 in the form of a 3 + 1 2 π b + 2 4 π 2 c − 1 .
Notice that 1 2 π 2 = ( 1 − 1 ) + 1 2 π ⋅ 0 + 2 4 π 2 ⋅ 2 . So a 3 = 1 , b = 0 , c = 2 ⇒ c a + b = 2 0 + 3 = 8 .